Norsk-russiske vitenskapelige relasjoner innen arktisk forskning 1814-1914 - Myklebost, Kari Aga (Nordlit, 2012)
Norway and Russia are both northern states, who administer vast maritime zones and land territories in the Arctic. Because of this, in both states we find a distinct northern focus that has occupied a prominent place, not least inside the field of sciences over the last two centuries. During the last decades of the 19th century there developed a handful of so to say specific arctic research disciplines, such as Arctic oceanographic studies, meteorology, auroral research, and also fishery related research.Throughout the different sub disciplines of arctic research, Norwegian and Russian scientists have held parallel research interests over the last two centuries. This hasled to a strongly felt need for exchange of data and knowledge across the border, and also a desire to conduct transnational studies. The article explores the border crossing Norwegian-Russian scientific networks in arctic research through the 19th century.